The Orientation of Physical Image Production Based Hotel Development in Urban Heritage Tourism Destination: Drawing Experiences from Hotels Along the Philosophical Axis Area, Special Region of Yogyakarta - Khusnul Bayu Aji (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2020)
The purpose of this study is to investigate the spatial distribution of hotels along the Philosophical Axis1 area of the Special Region of Yogyakarta, as well as their orientation development in terms of physical visualization. DIY – a popular nickname for the Special Region of Yogyakarta – is one of Indonesia’s culturally based tourist destinations. There is a Philosophical Axis in the spatial framework that is characterized by buildings and places that are in a straight line and serve as landmarks, namely Tugu, Kraton Yogyakarta, and Panggung Krapyak. Today, all three structures serve as tourist attractions. These circumstances lead to an increase in the sharing of tourism facilities in the surrounding buildings, one of which is represented by the hotel’s existence. Hotel is pivotal to note because it is classified as one type of amenity that supported the running of tourism activities, and its existence can be seen and placed at a specific location, so that it is identical to the spatial context. This is a descriptive study with a qualitative research approach. It collects primary data through observation and mapping, and secondary data through literature reviews related to the research’s focus and scope. According to the findings of this study, there are more hotels in the core zone of the Philosophical Axis area in terms of quantity. Meanwhile, the orientation of hotel establishments located at the Philosophical Axis area in terms of producing a physical visual image is largely the same, regardless of whether they are international or national hotel chains; or whether they are located on the Philosophical Axis’ main lane or not. In the case of independent hotels, only those in the main lane made significant efforts to physically synchronize with the image of the Philosophical Axis area.